EFL Students’ Perceptions of Pocket Book Use in Vocabulary and Speaking Development: A Case Study - Oktavia, Anida Feni; Susilowati, Tintin (FOSTER: Journal of English Language Teaching, 2026)
Vocabulary mastery is a major problem for EFL learners, especially in the active use of vocabulary in speaking skills. This problem is often caused by teaching materials that are not practical, less contextual, and do not support independent learning. Therefore, this research aimed to explore EFL students' perceptions of the use of pocket books in vocabulary and speaking skills. This study used a qualitative case study design involving 24 students who are members of the Language Student Activity Unit at universities. Data was collected through interviews and supported by questionnaire data, then analyzed using an interactive model. The results of the study show that students view pocket books as a medium that helps enrich vocabulary and speaking practice. Clear layouts, concise explanations, and ready-to-use phrases help reduce cognitive burden and support vocabulary memory, fluency, and student confidence. The novelty of this research lies in its focus on EFL students at the university level regarding the use of pocket books for vocabulary enrichment and speaking practice in the context of language learning outside the classroom. The results of this study show that pocket books have the potential to be an effective supporting learning medium to improve vocabulary mastery and speaking skills.